The Effect of Search, Solve, Create and Share Learning Models to Improve Students 'Critical Thinking Skills on Acid and Basic Titration Materials - Siti Nur Arisa; Ibnu Khaldun; Safrida Safrida (Postgraduate, University of Mataram, 2021)
This study aims to determine the improvement of students 'critical thinking skills in the acid-base titration material and to know the description of students' responses to learning to search, solve, create, and share. This study used an experimental method, comparing the experimental group with the control group through the pretest-posttest design, carried out at MAN 1 Aceh Barat. The sample selection used purposive sampling technique. The study population was class XI-IPA for the 2019/2020 school year and the samples were class XI-IPA2 (experimental group) and XI-IPA6 (control group). Data collection was carried out by giving a pretest and posttest to determine the increase in critical thinking skills. The results showed that the experimental group had an increase in the critical thinking component focusing on indicator questions with an average N-gain percentage of 74.58% in the high category, while other critical thinking components experienced an increase in the moderate category. Based on the t test, the posttest value of the experimental and control groups has a significant difference with tcount 2.107> ttable 2.093. This difference is influenced by the search, solve, create, and share model of the acid-base titration material in the experimental group. Students gave positive responses to learning to search, solve, create, and share with a percentage of 81.7% with the interested category. So, it is concluded that learning the search, solve, create, and share model can improve students' critical thinking skills on acid-base titration material